The Effect of Weight on Labor Market Outcomes: An Application of Genetic Instrumental Variables - Petri Böckerman; John Cawley; Jutta Viinikainen; Terho Lehtimäki; Suvi Rovio; Ilkka Seppälä; Jaakko Pehkonen; Olli Raitakari (Institute for the Study of Labor (IZA), 2016)
The increase in the prevalence of obesity worldwide has led to great interest in the economic consequences of obesity, but valid and powerful instruments for obesity, which are needed to estimate its causal effects, are rare. This paper contributes to the literature by using a novel instrument: genetic risk score, which reflects the predisposition to higher body mass index across many genetic loci. We estimate IV models of the effect of BMI on labor market outcomes using Finnish data that have many strengths: genetic information, measured body mass index, and administrative earnings records that are free of the problems associated with nonresponse, self-reporting error or top-coding. The first stage of the IV models indicate that genetic risk score is a powerful instrument, and the available evidence from the genetics literature is consistent with instrument validity. The results of the IV models indicate weight reduces earnings and employment and increases social income transfers, although we caution that the results are based on small samples, and are sensitive to specification and subsample.
Keywords: I10; J23; J31; 330; obesity; BMI; earnings; employment; genetic instruments